2022
DOI: 10.1002/leap.1437
|View full text |Cite
|
Sign up to set email alerts
|

Research data policies of journals in the Chinese Science Citation Database based on the language, publisher, discipline, access model and metrics

Abstract: This article investigates the research data policies of China's scholarly journals to provide a regional perspective. In total, 1243 science, technology, and medicine (STM) journals in the Chinese Science Citation Database (CSCD) were examined in June and July of 2021. The findings show that the existence and attitudinal strength of the research data policies of China's scholarly journals are weak overall, but differences exist across journals with different languages, publishers, disciplines, access models an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In terms of countries, higher percentages of journals from China, Hong Kong, and Singapore were found to adopt data sharing policies than those from other countries. Regulations and policies requiring data sharing recently established by government bodies in China [8] and Singapore [15] may have facilitated the establishment of data sharing policies by journals in these countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of countries, higher percentages of journals from China, Hong Kong, and Singapore were found to adopt data sharing policies than those from other countries. Regulations and policies requiring data sharing recently established by government bodies in China [8] and Singapore [15] may have facilitated the establishment of data sharing policies by journals in these countries.…”
Section: Discussionmentioning
confidence: 99%
“…The impact factor has been the most frequently mentioned factor, as journals with higher impact factors are more likely to have data sharing policies [3][4][5]. Regarding disciplines, it has been suggested that journals in the life sciences tend to adopt data sharing policies [4] or have stronger data sharing policies than those in other disciplines [6][7][8].…”
Section: Background/rationalementioning
confidence: 99%
See 2 more Smart Citations
“…Chinese language and literature is an essential basic course in the college classroom [9][10]. Literature [11] analyzed the strategic efforts of New Zealand students in Chinese language and literature learning, and the results showed that through group conversation and online communication, international students' Chinese language and literature learning ability can be effectively promoted, and their strategic efforts are also reflected.…”
Section: ) Chinese Language and Literaturementioning
confidence: 99%